Digital Islamic Financial Literacy and Inclusion on Profitability of Micro, Small and Medium Enterprises - Devi Pranatasari; Dhidhin Noer Ady Rahmanto; Ragil Satria Wicaksana (NUsantara Islamic Economic Journal, 2022)
Digital Islamic financial literacy and inclusion are the main factors in playing a role in increasing the profitability of Microfinance Microfinance Enterprises (MSMEs). This study uses a quantitative approach, data collection techniques using questionnaires, and the data source of this research is the owners of MSMEs in Bantul. Based on the results of this study, it is stated that digital Islamic financial literacy has a positive and significant effect on the profitability of MSMEs in Bantul, while digital Islamic financial inclusion has no significant effect on the profitability of MSMEs in Bantul. Taken together, digital Islamic financial literacy and inclusion simultaneously affect the profitability of MSMEs in Bantul. Limitations in this study are the limitations of two variables that affect profitability, of course, many variables affect profitability, and the sample in this study is only limited to Bantul.